Acute-Onset Visual Impairment in Wilson's Disease: A Case Report and Literature Review - Zheng, Zi-Wei; Xu, Meng-Hui; Sun, Chuan-Bin; Wu, Zhi-Ying; Dong, Yi (Frontiers in Neurology, 2022)
Objective: We reported one case of Wilson's disease (WD) patient with acute-onset visual impairment and summarized previously reported cases, to make physicians aware of the complicated clinical expressions of WD and improve diagnosis efficiency. Methods: The patient was recruited from the Second Affiliated Hospital of Zhejiang University School of Medicine. Clinical data, including cranial images, laboratory tests, and ophthalmic findings were obtained. The PubMed databases were searched for published cases of WD with visual impairment. Results: We reported a 22-year-old male who presented with hands tremor, personality change, and acute-onset binocular vision blurring. WD was considered to be closely correlated with neuropsychiatric and ocular involvement. After a low-copper diet and regular copper-chelation therapy, the related symptoms improved from before. Six WD cases of optic neuropathy have been reported, including our case. These patients usually had neurological and/or hepatic symptoms for a period without any treatment. All reported cases manifested as acute episodes of visual changes and the ocular manifestations improved after copper-chelation treatment. Conclusions: Excess copper accumulation may be a rare cause of visual impairment in WD patients. While the etiology behind patients' acute-onset visual impairment remained uncertain, the possibility of WD should be considered through neuropsychiatric and hepatic symptoms, corneal K-F rings, decreased serum ceruloplasmin, and a low likelihood or exclusion of other causes. Clinicians need to recognize this rare manifestation and give appropriate treatment to avoid misdiagnosis and unnecessary overtreatment.